Detección y seguimiento de personas mediante técnicas de fitlrado - Navarrete Hernández, Alberto (My University, 2016)
Detección y seguimiento de personas mediante técnicas de fitlrado
Keywords: Detección y seguimiento de personas mediante técnicas de fitlrado